A laser–laser method for carbonate C and O isotope measurement, metrology assessment, and stratigraphic applications - Petitjean, Alban; Thomazo, Christophe; Musset, Olivier; Jovovic, Ivan; Sansjofre, Pierre; Kirsimäe, Kalle (Frontiers in Geochemistry, 2024)
The stable isotopic compositions of carbon and oxygen (δ13Ccarb and δ18Ocarb) measured from carbonates are widely used in geology, notably to reconstruct paleotemperatures and the secular evolution of the biogeochemical carbon cycle, to characterize limestone sediment diagenesis, and to provide chemostratigraphy records. The standard technique used since the mid-20th century to measure C and O isotopic ratios is based on a wet chemical acid digestion protocol in order to evolve CO2 from carbonates—the latter being analyzed by mass spectrometry and, more recently, infrared spectroscopy. A newly developed laser-based method aims to circumvent this chemical preparation step by producing CO2 via an instant and spatially resolved calcination reaction. We describe an evolution of the laser calcination benchtop system previously described and used as a proof of concept toward a portable system, and we present the efficiency of this tool for performing carbon and oxygen isotope measurements from carbonate matrixes following standard evaluation metrology protocol. This metrological study explores the following: i) the use of internal standards; ii) inter-calibration with the traditional acid chemical preparation method; iii) analysis of the uncertainties of using GUM and ANOVA. Using 15 different types of carbonate minerals encompassing a range of isotopic VPDB compositions between −18.6‰ and +16.06‰ and between −14.80‰ and −1.72‰ for δ13Ccarb and δ18Ocarb, we show that isotopic cross-calibration is verified for both carbon and oxygen, respectively, and we demonstrate that the uncertainties (1σ) of the δ13Ccarb and δ18Ocarb measurements of laser–laser isotopic analysis are within 0.41‰ and 0.68‰, respectively. The advantages of this method in saving time and spatially resolved and automated analysis in situ are demonstrated by high-resolution chemostratigraphic analysis of a laminated lacustrine travertine sample.